In the country of others - Slimani, Leïla, 1981- (Slimani, Leïla, 1981- War, war, war, 2021)
"In her first new novel since The Perfect Nanny launched her onto the world stage and won her acclaim for her "devastatingly perceptive character studies" (The New York Times Book Review), Leila Slimani draws on her own family's inspiring story for the first volume in a planned trilogy about race, resilience, and women's empowerment. Mathilde, a spirited young Frenchwoman, falls in love with Amine, a handsome Moroccan soldier in the French army during World War II. After the war, the couple settles in Morocco. While Amine tries to cultivate his family farm's rocky terrain, Mathilde feels her vitality sapped by the isolation, the harsh climate, the lack of money, and the mistrust she inspires as a foreigner. Left increasingly alone to raise her two children in a world whose rules she does not understand, and with her daughter taunted at school by rich French girls for her secondhand clothes and unruly hair, Mathilde goes from being reduced to a farmer's wife to defying the country's chauvinism and repressive social codes by offering medical services to the rural population. As tensions mount between the Moroccans and the French colonists, Amine finds himself caught in the crossfire: in solidarity with his Moroccan workers yet also a landowner, despised by the French yet married to a Frenchwoman, and proud of his wife's resolve but ashamed by her refusal to be subjugated. All of them live in the country of others--especially the women, forced to live in the land of men--and with this novel, Leila Slimani issues the first salvo in their emancipation"--